Theoretical Studies on the Dynamical Behavior of Atom/Ion Migration on the Surface of Pristine and BN-Doped Graphene - Tong-Kun Zhang; Li-Jun Zhou; Jian-Gang Guo (C)
Using the potential function method, a theoretical model of the interaction was presented, and the interaction force between atoms/ions and (doped) graphene was obtained. Based on the interaction force, the dynamical control equation of atom/ion migration was derived. The dynamical behavior of atom/ion migrating on finite-size graphene surfaces along a specific direction and the regulation of boron nitride (BN) doping on the migration behavior were studied. The results show that the atoms/ions exhibit different migration mechanical behaviors due to different lateral forces inside and at the edges of the graphene surface. In addition, near the normal equilibrium height, atoms/ions are mainly affected by the lateral force, and their migration behavior is also influenced by the initial position, initial height, initial lateral velocity, etc. Furthermore, BN doping can affect the energy barrier of atom/ion migration on the graphene surface and effectively regulate the migration behavior of atoms/ions at the edge of the graphene surface. The research results can provide a theoretical reference for graphene surface localization modification and graphene-based atom/ion screening and detection.